2016
DOI: 10.21608/jppp.2016.52019
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Some Micronutrients and Plant Extracts of Resistance to Powdery Mildew and Nutrition Dill Plants in The Gharbiyah Governorate

Abstract: This work was carried out during the two successive seasons of 2014/ 2015 and 2015 / 2016 at Private Farm in Sammnoud, Gharbiyah Governorate, Egypt, to investigate the utilization of some micronutrients (Zn and Mn) and plant extracts [garlic (Allium sativum L) and aloe (Aloe vera)] and their effects on plant growth, yield (fruit essential oil), chemical composition and control against powdery mildew (Erysiphe heraclei) in dill plants. The application of plant extracts with micronutrients showed increased plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…These effects can also be due to the influence of garlic extract on growing levels of endogenous hormones in treated plants, (Khedr and Farid, 2000). These observations were consistent with (AbdelKader et al, 2014), (Ziedan and Eisa, 2016) on Anethum graveolens (Massoud et al, 2017) on Majorana hortensis L. plant. (El-Said and Ali, 2013) on Cumin.…”
Section: Discussionsupporting
confidence: 87%
“…These effects can also be due to the influence of garlic extract on growing levels of endogenous hormones in treated plants, (Khedr and Farid, 2000). These observations were consistent with (AbdelKader et al, 2014), (Ziedan and Eisa, 2016) on Anethum graveolens (Massoud et al, 2017) on Majorana hortensis L. plant. (El-Said and Ali, 2013) on Cumin.…”
Section: Discussionsupporting
confidence: 87%
“…Garlic extract (Allium sativum) is rich in macro and micro elements, important plant hormones like Auxins, Gibberellins and Cytokinin which induce cell division and increasing cell enlargement and lead to balance of physiological and biological processes and increasing photosynthesis processes and improving growth qualities (Hanafy et al, 2012, Nour Eldeen, 2014and Ziedan and Eisa, 2016. The objective of the current study was to study the effect of some biofertilizers, active dry yeast and garlic extract as well as their combination on growth, essential oil and chemical composition of marjoram plant.…”
Section: Introductionmentioning
confidence: 99%
“…These effects can also be caused by the impact on the growth of the endogenous hormones all in treated plants of garlic extract; (Abd-Allah et al, 2021). These observations corresponded to (Ziedan and Eisa, 2016) on dill plant who concluded that using garlic extract with micronutrients to have better yield from fruit, it is easily available, environmentally safe and cost-effective, (Massoud et al, 2017) on Majorana hortensis L. (Massoud et al, 2019) on Caraway and(AbdelKader et al, 2014), on Salvia officinalis L. Also the increases of photosynthetic pigment content, maybe due to a higher soil and nutrient retention and supply. This increase in photosynthetic pigment creation could also be a result of Azolla cytokinins' ability to prolong leaf aging by inhibiting chlorophyll breakdown and promoting protein and RNA synthesis (Castelfranco and Beale, 1983).…”
Section: Discussionmentioning
confidence: 74%